Low-dose Initiation of Buprenorphine/naloxone for the Management of Chronic Non-cancer Pain in Patients on Long-term Opioid Therapy: A Case Series - Maya Rattanavong; Donica Kwan; Derek Jorgenson; Eric Landry; Radhika Marwah; Katelyn Halpape (Taylor & Francis Group, 2024)
ABSTRACTBackground Buprenorphine may provide superior analgesia to full opioid agonist therapy and reverse the effects of opioid-induced hyperalgesia, while having a favorable safety profile and fewer adverse effects, in chronic non-cancer pain treatment. Low-dose initiation of buprenorphine is a useful strategy for patients on long-term opioid therapy because it avoids the need for moderate opioid withdrawal required for traditional buprenorphine initiations. However, there are few published reports of low-dose initiation regimens in the setting of chronic pain.Aims The aim of the study was to describe a case series of individuals living with chronic pain who were transitioned from long-term full opioid agonist therapy onto sublingual buprenorphine/naloxone using low-dose initiation regimens.Methods This study is a retrospective case series that included all patients who received care at an outpatient chronic pain clinic and were scheduled for low-dose initiation of buprenorphine/naloxone between March 2020 and December 2022. Data were collected through a retrospective review of electronic medical records and results were analyzed using descriptive statistics.Results Eighteen patients underwent transitions from their baseline opioids onto buprenorphine/naloxone using a low-dose initiation regimen. Of those patients, 17 successfully completed the initiation (94.44%), 12 experienced adverse effects during the initiation (66.67%), with only one patient requiring treatment discontinuation, and all adverse effects resolved once maintenance doses of buprenorphine/naloxone were established. The mean Clinical Global Impression-Improvement score after initiation was 2 (1-5).Conclusion Low-dose initiation is an effective approach to transition patients with chronic non-cancer pain from long-term opioid therapy to buprenorphine/naloxone without major complications or worsening pain.